Nigerians in poverty consume little wheat and wheat self-sufficiency programmes will not protect them from price shocks related to the Russia–Ukraine conflict - Liverpool-Tasie, Saweda Lenis Onipede; Reardon, Thomas; Parkhi, C.M.; Dolislager, M. (Springer, 2023)
The Russia–Ukraine conflict has prompted calls for resource diversification and wheat self-sufficiency programmes in import-dependent regions. Here we show that this approach would have minimal impact on poor Nigerians as wheat constitutes only 4% of their total food consumption and 8% of their starchy staple consumption. In contrast, millets, rice, cassava and tubers are ten times more important—highlighting the need for careful consideration of country-context consumption patterns in response to external food system shocks.